2013
DOI: 10.1186/1478-811x-11-80
|View full text |Cite
|
Sign up to set email alerts
|

HIF-1α activation results in actin cytoskeleton reorganization and modulation of Rac-1 signaling in endothelial cells

Abstract: BackgroundHypoxia is a major driving force in vascularization and vascular remodeling. Pharmacological inhibition of prolyl hydroxylases (PHDs) leads to an oxygen-independent and long-lasting activation of hypoxia-inducible factors (HIFs). Whereas effects of HIF-stabilization on transcriptional responses have been thoroughly investigated in endothelial cells, the molecular details of cytoskeletal changes elicited by PHD-inhibition remain largely unknown. To investigate this important aspect of PHD-inhibition, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 56 publications
2
25
0
1
Order By: Relevance
“…Cells were cultured at 37 °C and 7.5 % CO 2 in Dulbecco’s modified Eagle’s medium (DMEM) containing 10 % fetal calf serum (FCS) and routinely split in a 1:5 ratio. The stable knockdown of HIF-1α was induced by lentiviral transduction with shRNA producing constructs as described previously [21]. Cells with stable knockdown of HIF-1α (shHIF-1α) were compared to cells with stable transfection of an irrelevant shRNA (shGFP).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cells were cultured at 37 °C and 7.5 % CO 2 in Dulbecco’s modified Eagle’s medium (DMEM) containing 10 % fetal calf serum (FCS) and routinely split in a 1:5 ratio. The stable knockdown of HIF-1α was induced by lentiviral transduction with shRNA producing constructs as described previously [21]. Cells with stable knockdown of HIF-1α (shHIF-1α) were compared to cells with stable transfection of an irrelevant shRNA (shGFP).…”
Section: Methodsmentioning
confidence: 99%
“…Sections were counterstained with DAPI (1:5000; Life Technologies). Immunoblots were performed as described [21]. …”
Section: Methodsmentioning
confidence: 99%
“…Ïðè ýòîì îòìå÷àåòñÿ î÷åíü áûñòðàÿ äåñòàáèëèçàöèÿ áåëêîâ ïëîòíûõ êîíòàêòîâ, ïîâðåaeäå-íèå ýíäîòåëèîöèòîâ è àêòèâèçàöèÿ ìèãðàöèè ëåéêîöè-òîâ â òêàíü ãîëîâíîãî ìîçãà.  ðàáîòå [77] äîêàçàíî, ÷òî èñïîëüçîâàíèå èíãèáèòîðîâ Rac1 ïðè ñîõðàíåíèè àêòèâíîñòè HIF-1 ïðèâîäèò ê ñòàáèëèçàöèè ìåaeêëå-òî÷íûõ êîíòàêòîâ ýíäîòåëèîöèòîâ è óìåíüøåíèþ ìè-ãðàöèè êëåòîê â òêàíü ãîëîâíîãî ìîçãà.  ñâîþ î÷å-ðåäü, èìåþòñÿ äîêàçàòåëüñòâà òîãî, ÷òî Rac1 ÿâëÿåòñÿ îäíèì èç èíäóöèðóþùèõ è àêòèâèðóþùèõ ôàêòîðîâ äëÿ HIF-1.…”
Section: ìîëåêóëû Hif-1-àññîöèèðîâàííûõ ñèãíàëüíûõ ïóòåéunclassified
“…Wessel et al showed that Tyr685 and Tyr731 of VE-cadherin distinctly and selectively regulate the induction of vascular permeability or leukocyte extravasation [12]. Meanwhile, several factors have been reported to induce phosphorylation of tyrosine of the VE-cadherin including VEGF, TNF- α , and HIF-1 α , which may subsequently result in elevation of vascular permeability [1315]. Our previous study revealed that the serum Angiotensin (AngII) was remarkably elevated in AAD patients, together with elevation of pulmonary vascular permeability.…”
Section: Introductionmentioning
confidence: 99%